HUBUNGAN GAYA HIDUP DAN POLA MAKAN DENGAN STATUS GIZI PADA LANSIA DI WILAYAH KERJA PUSKESMAS BELAKANG PADANG KOTA BATAM - Gaol, Silvia Septiani Lumban; Gemini, Savitri; Badar, Mawardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The nutritional status of the elderly is the state of the elderly determined by the degree of physical need for energy and nutrients obtained from food and food whose physical impact can be measured. Comparison of the calculation of the average nutritional needs with the amount of nutrient intake can provide an indication of the presence or absence of nutritional problems. In 2020 the elderly population is around 9.3 % and in 2050 it is estimed that the number of elderly will reach,According to the 2021 health office data belakang padang occupies the second largest health center which has 2,876 elderly people. The purpose of this study was to determine the relationship between lifestyle and diet with nutritional status in the elderly in the Belakang Padang Health Center working area, Batam City in 2023.This research is an observational analytic study on two groups of variables with quantitative methods and with a crosssectional approach and the sampling technique used is random sampling, the result showed that normal nutritional status mostly occurred in a healthy lifestyle of 24 elderly (36,4%) and normal nutritional status mostly had a good diet of 26 elderly (39,4%).The results of this study can educational material and knowledge.Keywords: Lifestyle,diet, nutritional status,elderly.